Location selection of hydrogen refuelling stations - Geçici, Ebru. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2021., 2021)
The energy resources used today will not be sufficient to fulfil the future demand and the transportation sector will also be affected. Researchers, therefore, study alternative energy sources. Through its advantages, hydrogen energy constitutes one of these alternatives. Hydrogen, which can be used as fuel in vehicles, constitutes an important alternative with electric vehicles for the future. Through its infrastructure advantages, electric vehicles have been on the market before and therefore have a higher rate of sales today. However, with the development of hydrogen technology and the reduction in its costs, it is foreseen that hydrogen vehicles will take their place in the market. This situation is promoted by the countries' support programs published for the development of hydrogen energy, and hydrogen fuel cell vehicle (HFCV) produced by the companies that have an important share in the automobile industry. However, in order for HFCV to become widespread, the number of hydrogen refuelling stations (HRSs) should increase. Electric vehicles can recharge their batteries at points such as homes, which eliminates the need to open a dedicated charging station. However, it is compulsory to open HRSs, where HFCVs can be fuelled. Therefore it is critical to locate HRS. In this thesis, we aim to determine the locations of the HRSs. In this context, the locations of HRSs to be opened in Istanbul are determined using a multiperiod p-median model. In order to determine the future demand, the adaptation of demand points (i.e., neighbourhoods) to hydrogen technology is taken into account by using the development indexes of the districts. According to the results, it is observed that in the first periods, the HRSs are opened in the center and they are spread throughout the city in the later periods of a 30-year planing horizon.
Keywords: Hydrogen as fuel.